Error probability performance analysis for multicarrier direct sequence code division multiple access multiple-input-multiple-output systems over correlated Î·-Î¼ fading channels - Amok, J.O.M. (Institution of Engineering and Technology, 2014)
The authors investigate the performance of multiple-input-multiple-output multicarrier direct sequence code division multiple access system operating over arbitrarily and equally correlated Î·-Î¼ fading channels in terms of average bit error probability and average symbol error probability. Closed form expressions for average error probability using moment generating function-based approach are derived and expressed in terms of Lauricella's multivariate hypergeometric functions. Furthermore, based on numerical results, they observe that the performance of the system improves when the number of multipath clusters increases as well as the number of subcarriers (frequency diversity). Similarly, substantial enhancement in system performance is observed due to the effect of spatial diversity. Finally, they verify the results via Monte Carlo simulation-based method to support the accuracy of the analytical approach and also compare with already published ones. Â© The Institution of Engineering and Technology 2014.